Optimization of cassava peel medium to an enriched animal feed by the white rot fungi Panus tigrinus M609RQ - Ruqayyah, Tijani I.D.; Jamal, Parveen; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (2011)
Media components such as wheat flour, MgSO4 and particle size were screened by Placket Burman design (PBD) while the operating range was fixed by one-factor-at-a-time method (OFAT), primarily for the enrichment of cassava peels as animal feed. Optimization of the selected media components was carried out using Face–Centered Central Composite Design (FCCCD) of the Response Surface Methodology (RSM) and the responses were measured in term of protein and lignin contents. Statistical analysis of the result showed that the quadratic term of wheat flour and the interaction between wheat flour and particle size were highly significant (P<0.01) for protein content, while for lignin degradation, MgSO4 and particle size were significant (p< 0.05) in their linear term. The validated result showed that the optimum media component for the production of an enriched cassava peel by the white rot fungus Panus tigrinus (M609RQY) was wheat flour 4.30% (w/w), 0.45 g/kg MgSO4, and using 1 mm particle size. This resulted to 77.83% increase in protein and 52.62% lignin degradation, thus indicating the potency of the white rot fungus Panus tigrinus for the production of economical livestock feed from renewable source.